GPS phase scintillation associated with optical auroral emissions: First statistical results from the geographic South Pole. Issue 5 (15th May 2013) - Kinrade, Joe; Mitchell, Cathryn N.; Smith, Nathan D.; Ebihara, Yusuke; Weatherwax, Allan T.; Bust, Gary S.
Abstract : [1] Ionospheric irregularities affect the propagation of Global Navigation Satellite System (GNSS) signals, causing radio scintillation. Particle precipitation from the magnetosphere into the ionosphere, following solar activity, is an important production mechanism for ionospheric irregularities. Particle precipitation also causes the aurorae. However, the correlation of aurorae and GNSS scintillation events is not well established in literature. This study examines optical auroral events during 2010–2011 and reports spatial and temporal correlations with Global Positioning System (GPS) L1 phase fluctuations using instrumentation located at South Pole Station. An all‐sky imager provides a measure of optical emission intensities ([OI] 557.7 nm and 630.0 nm) at auroral latitudes during the winter months. A collocated GPS antenna and scintillation receiver facilitates superimposition of auroral images and GPS signal measurements. Correlation statistics are produced by tracking emission intensities and GPS L1 σφ indices at E and F‐region heights. This is the first time that multi‐wavelength auroral images have been compared with scintillation measurements in this way. Correlation levels of up to 74% are observed during 2–3 hour periods of discrete arc structuring. Analysis revealed that higher values of emission intensity corresponded with elevated levels of σφ . The study has yielded the first statistical evidence supporting the previously assumed relationship between the aurorae and GPS signal propagation. The probability of scintillation‐induced GPS outages is of interest for commercial and safety‐critical operations at high latitudes. Results in this paper indicate that image databases of optical auroral emissions could be used to assess the likelihood of multiple satellite scintillation activity. Key Points: Collocated GPS scintillation receiver and all‐sky imager at the South Pole First statistics from simultaneous tracking of GPS signals and optical aurorae GPS phase scintillation correlates closely at times with discrete auroral arcs